Sanctifying of represivnoy activity of organs of state security of the USSR in Donbase in a post-war period in modern Ukrainian historiography - Olena Luhova (Cхід, 2013)
In the article the basic historiography tendencies of study of political repressions of post-war times are probed in Donbasse. An author analyses the publications of researchers, which, using different approaches, tried to find out motion and scales of activity of organs of state security of theUSSRafter war at regional level. Іn the article on the basis of analysis of modern Ukrainian historiography on questions repressive activity of organs of state security of the USSR in Donbas there is absence of complex research of regional level of political repressions in post-war days